Polysemy and Metaphorical Extensions of Temperature Terms: Warm and Cool - Truly Almendo Pasaribu (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This study focuses on describing the concept and the extended senses of warm and cool in English. As these temperature terms contain more than one semantic representation, this study aims at finding out the prototypical meaning, the extended senses, and the relation between the prototypical meaning and the extended senses of these lexemes. The word warm has three extended senses, namely: (1) friendly, (2) pleasant to other senses, and (3) near the goal of the game. Furthermore, the word cool whose prototypical meaning is â€œhaving a low temperatureâ€ has four senses, namely: (1) calm, (2) unfriendly, (3) fashionable and (4) agreeable. These three words which are originally expressed to describe the degree of heat are extended to describe other human physical experience. The extension of those senses is motivated by metaphors as the temperature domain is pervasive to express non-temperature entity. The discussion highlights the relations between the central sense and the extended ones. The relation of the senses enables us to draw the semantic networks of polysemy warm and cool.